2010
DOI: 10.1590/s1679-45082010ao1342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pain in outpatient diagnostic hysteroscopy with gas

Abstract: Objective: To evaluate the intensity of pain reported by patients undergoing outpatient diagnostic hysteroscopy. Methods: Exam performed with a 5-mm lens hysteroscope, vaginal speculum, tenaculum and uterine distention with carbon dioxide gas. Before and after the examination, patients were interviewed to define, in a verbal scale from 0 to 10, pain values that they expected to feel and that they experienced after the end, and also if they would repeat it if indicated. Data were analyzed using Statistical Pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[17][18][19][20]22,27 According to Dinz et al the test could be more tolerable if the patients were instructed in a more detailed way, which was supposed to reduce the anxiety and the expectation regarding the procedure, being this the main hypothesis of the study. 13 On one hand, the present study showed that the more well-oriented patients presented slightly more pronounced pain rates, when the analysis was made with the percentage. On the other hand, if the categorization had been according to the averages of pain, the result could be different, which may be a justification for the difference of results between groups.…”
Section: Reproductive Healthmentioning
confidence: 47%
See 3 more Smart Citations
“…[17][18][19][20]22,27 According to Dinz et al the test could be more tolerable if the patients were instructed in a more detailed way, which was supposed to reduce the anxiety and the expectation regarding the procedure, being this the main hypothesis of the study. 13 On one hand, the present study showed that the more well-oriented patients presented slightly more pronounced pain rates, when the analysis was made with the percentage. On the other hand, if the categorization had been according to the averages of pain, the result could be different, which may be a justification for the difference of results between groups.…”
Section: Reproductive Healthmentioning
confidence: 47%
“…Comparative study of pain perception in outpatient hysteroscopy analyzing previous orientation by multimedia account by the doctor. 13,23,24 It is of extreme importance the concern with the tolerance and the discomfort made by the procedure, which many time are not taken into account. [17][18][19][20]22,27 According to Dinz et al the test could be more tolerable if the patients were instructed in a more detailed way, which was supposed to reduce the anxiety and the expectation regarding the procedure, being this the main hypothesis of the study.…”
Section: Reproductive Healthmentioning
confidence: 99%
See 2 more Smart Citations